2021
DOI: 10.1371/journal.pone.0259999
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of left atrial strain to predict atrial fibrillation recurrence after cryoballoon ablation

Abstract: Objective Atrial fibrillation (AF) recurrence occurs in approximately 25% of the patients undergoing cryoballoon ablation (CBA), leading to repeated ablations and complications. Left atrial (LA) dilation has been proposed as a predictor of AF recurrence. However, LA strain is a surrogate marker of LA mechanical dysfunction, which might appear before the enlargement of the LA. The purpose of this study was to evaluate the additional predictive value of LA function assessed using strain echocardiography for AF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
9
1
3
Order By: Relevance
“…20 In a previous study which is performed using 2D-STE method and includes the patients with persistent and paroxysmal AF, peak atrial longitudinal strain parameter which is measured before the procedure has been shown to be effective in predicting the AF recurrences occurring 3 months after the procedure in both patients with LA size in normal ranges and patients with an enlarged LA. 21 The results of our study detected no significant change in the parameters of diastolic functions. Despite the non-significant increase in the left atrial dimension, a significant improvement was detected in the parameters, LAsr and LAsct which shows the ability of compliance and contractility of the LA through the 2D-STE method.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…20 In a previous study which is performed using 2D-STE method and includes the patients with persistent and paroxysmal AF, peak atrial longitudinal strain parameter which is measured before the procedure has been shown to be effective in predicting the AF recurrences occurring 3 months after the procedure in both patients with LA size in normal ranges and patients with an enlarged LA. 21 The results of our study detected no significant change in the parameters of diastolic functions. Despite the non-significant increase in the left atrial dimension, a significant improvement was detected in the parameters, LAsr and LAsct which shows the ability of compliance and contractility of the LA through the 2D-STE method.…”
Section: Discussioncontrasting
confidence: 42%
“…LA strain and strain rate imaging using tracking of acoustic kernels by 2D‐STE, a novel angle‐independent tool for measuring myocardial stretch with the ability to quantitatively analyze global and regional LA contractility and relaxation, could therefore serve as a noninvasive tool to identify contractile dysfunction while overcoming the existing limitations of Doppler‐based technologies 20 . In a previous study which is performed using 2D‐STE method and includes the patients with persistent and paroxysmal AF, peak atrial longitudinal strain parameter which is measured before the procedure has been shown to be effective in predicting the AF recurrences occurring 3 months after the procedure in both patients with LA size in normal ranges and patients with an enlarged LA 21 . The results of our study detected no significant change in the parameters of diastolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…LA strain and strain rate imaging using tracking of acoustic kernels by 2D-STE, a novel angle-independent tool for measuring myocardial stretch with the ability to quantitatively analyze global and regional LA contractility and relaxation, could therefore serve as a noninvasive tool to identify contractile dysfunction while overcoming the existing limitations of Doppler-based technologies [19]. In a previous study which is performed using 2D-STE method and includes the patients with persistent and paroxysmal AF, peak atrial longitudinal strain parameter which is measured before the procedure has been shown to be effective in predicting the AF recurrences occurring 3 months after the procedure in both patients with LA size in normal ranges and patients with an enlarged LA [20]. The results of our study detected no signi cant change in the parameters of diastolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…The community of patients with AF recurrence is varied in terms of age, gender, structural heart disease, comorbidities such as hypertension and diabetes, history of congestive heart failure and embolic events, and type of AF, according to studies conducted over the years. 5,6 For instance, atrial fibrosis measured by LGE-CMR is associated with the probability of recurrence after cryoball ablation. 7,8 The study of left atrial appendage blood flow velocity as an independent risk factor for recurrence of AF by transesophageal echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a higher risk of postoperative recurrence can be identified through preoperative examination, thus improving the success rate and minimizing the dangers of the surgery. The community of patients with AF recurrence is varied in terms of age, gender, structural heart disease, comorbidities such as hypertension and diabetes, history of congestive heart failure and embolic events, and type of AF, according to studies conducted over the years 5,6 . For instance, atrial fibrosis measured by LGE‐CMR is associated with the probability of recurrence after cryoball ablation 7,8 .…”
Section: Introductionmentioning
confidence: 99%